2017
DOI: 10.1007/s00345-017-2163-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fosfomycin against fluoroquinolones for transrectal prostate biopsy prophylaxis: an individual patient-data meta-analysis

Abstract: Patients who received FT prophylaxis were less likely than those who received FQ prophylaxis to develop infections overall, as well as severe and resistant infections after TRUSPB. Assessing the performance of FT in other geographic locations or in comparison to targeted prophylaxis based on risk assessment or rectal cultures is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
1
35
0
2
Order By: Relevance
“…The benefit of FT reported here has been observed in other studies, including a meta‐analysis with 3112 patients that showed a significantly lower number of infectious complications in those treated with FT . Importantly, fewer infections were noted in patients who had confirmed FQ resistance and were given FT in preference to FQ.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The benefit of FT reported here has been observed in other studies, including a meta‐analysis with 3112 patients that showed a significantly lower number of infectious complications in those treated with FT . Importantly, fewer infections were noted in patients who had confirmed FQ resistance and were given FT in preference to FQ.…”
supporting
confidence: 77%
“…Concern regarding TRUSPB‐related infections despite antimicrobial prophylaxis, chiefly due to the development of fluoroquinolone (FQ) resistance, has prompted the development of adjunct prophylaxis methods and biopsy approaches . Fosfomycin trometamol (FT) has long been used in the USA and Europe with broad‐spectrum bactericidal coverage and adequate prostatic soft tissue concentrations, and has been shown to reduce TRUSPB‐related infections compared with FQ‐based prophylaxis …”
mentioning
confidence: 99%
“…Recently, several studies have investigated the potential of fosfomycin as a prophylactic antibiotic in prostate biopsies . Pooled results from five studies containing 3112 patients in a recent meta‐analysis showed that the relative odds of an infectious complication (OR 0.22, 95% CI 0.09–0.54) was significantly lower in those receiving fosfomycin compared with FQ prophylaxis . In the present study, 22 patients with FQ bacteria in the intervention group received fosfomycin without infectious complications after TRPB.…”
Section: Discussionmentioning
confidence: 64%
“…After a median follow up of 20 months, seven patients (47%) had a clinical response . Fosfomycin may also prove to be a useful alternative in the prevention of trans‐rectal ultrasound‐guided prostate biopsy‐related infectious complications in patients with a high risk of quinolone resistance …”
Section: Mechanism Of Action and Antimicrobial Activity And Resistancementioning
confidence: 99%